In-junction-plane beam divergence stabilization by lateral periodic structure in wide-stripe laser diodes - Andrzej Maląg; Grzegorz Sobczak; Elżbieta Dąbrowska; Marian Teodorczyk (AIMS Electronics and Electrical Engineering, 2019)
This paper describes the way to stabilize in-junction-plane optical field distribution and emitted beam divergence in high-power 970-nm-band laser diodes (LDs). This is done by introducing a lateral periodic structure into the LD‟s wide-stripe-waveguide, designed to prefer and stabilize the selected (resonant) high-order lateral mode. According to modeling, in CW operation the gain equalization of lateral modes due to thermal index guiding leads to beam divergence stabilization by incorporating the modes up to the resonant one and cutting out higher ones. This was demonstrated experimentally in a wide drive current range. Such stability of a non-Gaussian laser beam profile with steep slopes can be interesting for many applications. Thanks to the drive current flow control by the periodic structure, the effects typical for conventional wide-stripe LDs, such as lateral current crowding, carrier accumulation at stripe edges and optical far-field blooming are not observed.